Association of ABO blood group with Hypertension and BMI in a tertiary health care hospital - Jayker, Shushan Shweta; Devru , Nandini; Prakash, Prakash; Sunita, Sunita (Journal of Neonatal Surgery, 2025)
Introduction: Hypertension is a chronic medical condition and one of the most common life threatening non-communicable disease. Familial patterns of hypertension suggests genetic factor as another important non-modifiable predisposing factor, and ABO blood group is one of the such factor which needs to be studied in more detail. Objectives: To know the distribution of different blood groups among hypertensive patients. To assess the association between blood groups with Hypertension and BMI Material & Methods: This is a Prospective study done in ESIC medical college and hospital over a period of 3 months (Jan 2023 to Mar 2023). All adults of ≥ 18yrs of age and who were hypertensive (primary) were included in the study, wherein we had 300 cases. Along with blood pressure their height, weight and BMI was recorded. Blood grouping and Rh typing was done simultaneously. Pregnant women and patients with secondary hypertension were excluded from the study. Results: Blood group ‘O’was the most prevalent (n= 102; 34.0%) blood group in our study.This was followed by ‘A’ (n=93; 31.0%), ‘B’ (n=78; 26.0%) and ‘AB’ (n=27; 9.0%). The highest average values of systolic blood pressure (SBP) and diastolic blood pressure (DBP) were recorded in blood group ‘B’. The observed differences in the mean values of blood pressure (BP) indices across ABO blood groups were statistically significant. Maximum subjects with elevated blood pressure were found in blood group ‘B’ (n=78; 26.0%) and significant association was observed between ABO blood groups and Hypertension (p < 0.001). However, we did not find any significant association with BMI and gender among different blood groups. Conclusion: In conclusion, our results suggest that hypertensive patients were found to be highest in blood group ‘B’ and lowest in blood group ‘AB’. No correlation exists between the gender and BMI.